Blood pressure response to acute and chronic exercise in chronic kidney disease. Issue 1 (January 2017) - Headley, Samuel; Germain, Michael; Wood, Richard; Joubert, Jyovani; Milch, Charles; Evans, Elizabeth; Cornelius, Allen; Brewer, Britton; Taylor, Beth; Pescatello, Linda S.
Abstract: Aim: The current study was designed to determine if a relationship exists between acute and chronic blood pressure responses to aerobic exercise in pre‐dialysis patients. Methods: Pre‐dialysis kidney patients attended four sessions before being randomized to the treatment ( n = 25) or control group ( n = 21). In session 1, resting blood pressure was recorded, and these measurements were repeated during the second visit when peak oxygen uptake (VO2peak ) was assessed. In the third and fourth sessions, blood pressures were taken prior to a 40 min walk or period of seated rest. After the 40 min walk or seated rest, blood pressures were monitored for 60 min in the laboratory and for the subsequent 24 h. After session 4, subjects in the treatment group trained aerobically at a moderate intensity, three times per week for 16 weeks. Control subjects were asked to be sedentary. All measurements were repeated after 16 weeks of training or sedentary living. Results: Training increased VO2peak (mL/kg per minute) in the treatment group (baseline 19.6 ± 6.7 vs 21.2 ± 7.7, P < 0.05), with no change in the control (18.0 ± 6.0 vs 17.5 ± 5.7) group. Post‐exercise hypotension occurred at baseline prior to training but was unaffected by 16 weeks of training. Conclusion: Post‐exercise hypotension occurs in pre‐dialysis patients following aerobic exercise, but short‐term moderate‐intensity continuous aerobic training has no effect upon this response. There seems to be no relationship between the acute and chronic blood pressure responses to exercise in pre‐dialysis kidney patients. Summary at a Glance: Proof of concept study assessing BP response to exercise in pre‐dialysis CKD patients. BP measured by ABPM. Negative study but findings suggestive of attentauted hypotensive response to exercise.